Cyberbullying y desarrollo de socialización en estudiantes de educación inicial de la facultad de ciencias de la educación y humanidades de la Universidad Nacional de la Amazonía Peruana, Iquitos 2021 - Reategui Papa, Lucy Ibeth (2022)
The main reason of this study has been to determine the relationship between cyberbullying and the development of socialization in initial education students of the Faculty of Education Sciences and Humanities at the National University of the Peruvian Amazon located in the city of Iquitos in in 2021. As a methodology, the relational type of research has been used, through a field, cross-sectional, and bivariate design. The population consisted of 192 initial education students, the sample was census, that is, the 192 students. It was applied to the survey as a data collection technique and two questionnaires as instruments, which were validated at the appropriate time by the judgment of judges. When establishing the relationship between the variables cyberbullying and the development of socialization through the chi-square test, it is found to be = 228.85, with p=0.000, which indicates that there is a relationship between the variables cyberbullying and the development of socialization; In addition, Kendall's Tau-b coefficient = -0.775 shows that the relationship is direct, strong, and significant.